The Americanization of Arnold Schoenberg?. Theory, Analysis, and Reception - John Covach (Zeitschrift der Gesellschaft für Musiktheorie)
This article surveys the reception of Arnold Schoenberg’s theoretical ideas in English-language music theory, with a primary (though not exclusive) focus on their reception in the United States. William Rothstein has chronicled how Heinrich Schenker’s ideas were modified to conform to the American music-theoretical discourse (“Americanization”). The question then arises: Were Schoenberg’s theoretical ideas also similarly modified? After a preliminary overview of the availability of Schoenberg’s theoretical writing in English translation, four topics in Schoenberg’s thought are traced, with a focus on the post-war era: 1) harmony; 2) form; 3) thematic and motivic transformation; and 4) aesthetics. The American reception of Schoenberg’s theoretical ideas has tended to focus on the music-technical dimension of his theoretical texts and has, to a significant extent, ignored the more philosophical and aesthetic aspects of his thought. It has tended to place emphasis on how music is structured and how that structure is unified; there has been less concern with why such unity is important in a broader sense. // Dieser Aufsatz gibt einen Überblick über die Rezeption von Arnold Schönbergs theoretischem Denken in der englischsprachigen Musiktheorie, wobei der Fokus, wenn auch nicht ausschließlich, auf der Rezeption in den Vereinigten Staaten liegt. William Rothstein hat dargestellt, wie Heinrich Schenkers Theorie im Zuge einer Anpassung an den amerikanischen musiktheoretischen Diskurs modifiziert wurde (“Americanization”). Dies legt die Frage nahe, ob auch Schönbergs theoretisches Denken in ähnlicher Weise modifiziert worden ist. Nach einer einführenden Übersicht über die Verfügbarkeit von Schönbergs Schriften in englischen Übersetzungen werden vier Themenbereiche von Schönbergs Denken in der anglophonen Musiktheorie verfolgt, wobei der Schwerpunkt auf der Nachkriegszeit liegt: 1) Harmonik; 2) Form; 3) thematische und motivische Transformation; 4) Ästhetik. Die amerikanische Rezeption von Schönbergs Theorien tendierte dazu, die technischen Aspekte in seinen Schriften herauszustellen, und vernachlässigte dabei in einem signifikanten Ausmaß die stärker philosophischen und ästhetischen Aspekte seines Denkens. Die Schönberg-Rezeption in den USA hat also ein starkes Gewicht auf Fragen musikalischer Struktur und struktureller Einheit gelegt; weniger wurde hingegen danach gefragt, warum eine solche Einheit in einem umfassenderen Sinn erstrebenswert ist.